Reviewing the Show and Tell Method in Teaching Speaking Skills to Elementary School Students - Maratus Soliha; Yunika Afryaningsih; Salman Al-Farisi (Jurnal Pendidikan Indonesia, 2025)
This study aims to analyze the steps of the show and tell method in learning students' speaking skills in elementary school. This research focuses on the steps of the show and tell method which include (1) Showing concrete objects/images (show), (2) Students are guided to describe objects (tell), (3) Dividing students into groups, (4) In groups, students discuss the right sentences to describe the selected objects and have been shown in more detail, (5) In groups, students display the results of their work, namely showing and describing the objects they have chosen, and (6) The teacher guides other students to listen and respond. This research uses descriptive qualitative with the type of literature study research. The data collection technique used documentation with primary data sources in the form of 20 articles. The results of this research study found that there were 13 articles that explained the steps of the show and tell method and 7 other articles did not explain the steps of the show and tell method. Based on the analysis of the 20 articles, it shows that the show and tell method is very effective to improve the speaking skills of elementary school students. In addition, the application of the show and tell method has a good impact in fostering the courage to appear in front of the class, fostering public speaking skills from an early age, overcoming shyness, doubt, and feelings of fear experienced by students when expressing their opinions in front of classmates.